The Separation of Audit and Risk Committees and the Quality of Financial Reporting: A Qualitative Analysis of Regulatory Reforms Following the 2007-2009 Financial Crisis - Muhammad Rizal; Ruslaini Ruslaini; Yessica Amelia (LPPM STIE Kasih Bangsa, 2025)
This study explores the impact of separating audit and risk committees on financial reporting quality, emphasizing regulatory reforms introduced following the 2007–2009 financial crisis. Employing a qualitative literature review methodology, the research synthesizes findings from prior studies to evaluate the efficacy of these reforms in enhancing financial transparency and mitigating audit failures. The analysis reveals mixed outcomes, with evidence supporting the improved independence and oversight capabilities of segregated committees, while highlighting challenges such as resource constraints and evolving regulatory compliance demands. Comparative insights underscore variations across jurisdictions, emphasizing the importance of contextualizing governance practices. The study concludes with a discussion on the implications for policy and practice, alongside identified limitations and avenues for future research.